Association of clinical outcome assessments of mobility capacity and incident disability in community-dwelling older adults - a systematic review and meta-analysis - Braun, Tobias; Thiel, Christian; Peter, Raphael Simon; Bahns, Carolin; Büchele, Gisela; Rapp, Kilian; Becker, Clemens; Grüneberg, Christian (Ageing research reviews, 2022)
The objective of the present review is to synthesize all available research on the association between mobility capacity and incident disability in non-disabled older adults. MEDLINE, EMBASE and CINAHL databases were searched without any limits or restrictions until February 2021. Published reports of longitudinal cohort studies that estimated a direct association between baseline mobility capacity, assessed with a standardized outcome assessment, and subsequent development of disability, including initially non-disabled older adults were included. The risk of bias was assessed using the Quality in Prognosis Studies (QUIPS) tool. Random-effect models were used to explore the objective. The certainty of evidence was assessed using the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) approach. The main outcome measures were the pooled relative risks (RR) per one conventional unit per mobility assessment for incident disability. A total of 40 reports (85,515 participants at baseline) were included. For usual and fast gait speed, the RR per −0.1 m/s was 1.23 (95% CI: 1.18-1.28; 26,638 participants) and 1.28 (95% CI: 1.19-1.38; 8161 participants), respectively. Each point decrease in Short Physical Performance Battery score increased the risk of incident disability by 30% (RR = 1.30, 95% CI: 1.23-1.38; 9183 participants). The RR of incident disability by each second increase in Timed Up and Go test and Chair Rise Test performance was 1.15 (95% CI: 1.09-1.21; 30,426 participants) and 1.07 (95% CI: 1.04-1.10; 9450 participants), respectively. The review concludes that among community-dwelling non-disabled older adults, poor mobility capacity is a potent modifiable risk factor for incident disability. Mobility impairment should be mandated as a quality indicator of health for older people.